Computed tomography and magnetic resonance diagnosis of variations in the anatomical location of the major salivary glands in 1680 dogs and 187 cats. (March 2016) - Durand, A.; Finck, M.; Sullivan, M.; Hammond, G.
Highlights: Atypical salivary gland locations were assessed in a population of dogs and cats. Two percent of dogs had variations in the location of at least one mandibular gland. Fifty-eight percent of dogs with mandibular variations were Border Terriers. Approximately 0.2% of dogs had variations in the location of one zygomatic gland. No salivary gland variation was identified in cats. Abstract: During assessment of routine clinical magnetic resonance imaging (MRI) of the heads of dogs, variations in the location of mandibular and zygomatic salivary glands (SGs) were observed incidentally. The aims of this retrospective study were to describe anatomical variations of the major SGs found on MRI and computed tomography (CT) studies of the head in dogs and cats and to investigate possible clinical relevancy. No anatomical variation of the SGs was seen in cats, but in dogs, although variation of the parotid SG was not identified, that of the mandibular SG was found in 33/1680 animals (2%), either unilaterally (6/33 right-sided, 13/33 left-sided) or bilaterally (14/33). The Border terrier breed (19/33, 58%) was over-represented. Each atypically located mandibular SG was positioned medial to the digastric muscle and rostral to the retropharyngeal lymph node. The sublingual glands were difficult to delineate from the mandibular glands. Anatomical variation of one zygomatic gland (3/4 left-sided) was identified in four small-breed dogs (0.2%). Each atypically located zygomatic gland was tilted at the ventrorostral aspect of the masseter muscle underneath the skin surface. MRI and CT characteristics were not different between typically and atypically located SGs. None of the dogs had clinical signs related with SG disease. It was concluded that, with suspected breed predispositions, incidental unilateral or bilateral anatomical variations of mandibular and zygomatic SGs can be encountered in dogs and an awareness of these possible variations may be important in pre-surgical planning.